2012
DOI: 10.3390/molecules17044604
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Chitin from the Beetle Holotrichia parallela Motschulsky

Abstract: Insect chitin was isolated from adult Holotrichia parallela by treatment with 1 M HCl and 1 M NaOH, following by 1% potassium permanganate solution for decolorization. The yield of chitin from this species is 15%. This insect chitin was compared with the commercial α-chitin from shrimp, by infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and elemental analysis. Both chitins exhibited similar chemical structures and physicochemical properties. Adult H. parallela is thus a promising altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
210
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(245 citation statements)
references
References 19 publications
31
210
3
1
Order By: Relevance
“…The samples were then mineralized in a muffle furnace at 550 °C and the total amount of ash was measured. Additionally, chitin content was analysed according to Liu et al (2012) using hydrolysis with 1M hydrochloric acid and 1M sodium hydroxide. Because chitin is a nitrogenous polysaccharide, the nitrogen content was also analysed in these hydrolysed samples to refine total crude protein content.…”
Section: Analysis Of Proximate Compositionmentioning
confidence: 99%
“…The samples were then mineralized in a muffle furnace at 550 °C and the total amount of ash was measured. Additionally, chitin content was analysed according to Liu et al (2012) using hydrolysis with 1M hydrochloric acid and 1M sodium hydroxide. Because chitin is a nitrogenous polysaccharide, the nitrogen content was also analysed in these hydrolysed samples to refine total crude protein content.…”
Section: Analysis Of Proximate Compositionmentioning
confidence: 99%
“…In recent studies, 15-25% chitin has been isolated from the dried exoskeleton of Crustacea such as prawn, shrimp, crab and lobster [21][22][23]. It is noted that the chitin contents of the total body structure dry weight of insects including Agabus bipustulatus, Anax imperator, Bombyx mori, Holotrichia parallela, Hydrophilus piceus, Notonecta glauca, Ranatra linearis and silkworm chrysalides ranges from 10% to 20% among the different species [13,[24][25][26]. Alternatively, it was presented by Sajomsang and Gonil [27] that 36% of cicada sloughs were chitin.…”
Section: Resultsmentioning
confidence: 99%
“…While the CrI values of chitins isolated from organisms such as crab and insects in former studies were observed to be between 54 and 91% [13,26]. Moreover, it was observed that chitins isolated from fungi and resting eggs have quite low CrI values [11].…”
Section: Xrdmentioning
confidence: 94%
See 2 more Smart Citations